Using a Systems-Approach for Implementing a Smart Government Policy in Soppeng Regency - Mustafa, Delly; Maulana, A. Muhammad Fajar; Niswaty, Risma; Burhanuddin, Burhanuddin (KnE Social Sciences, 2022)
The Soppeng Regency Government has implemented a Smart Government Policy by utilizing information and communication technology, the use of which is regulated by the Soppeng Regent regulation number 87 of 2019. This study aimed to examine the implementation of the Smart Government Policy by the Soppeng Regency Government. This was a descriptive study which used a qualitative approach. Data were collected through observation, interviews, and documentation techniques. Triangulation was used to check the validity of the data. An interactive model was used to analyze the data. The results showed that the Smart Government Policy was implemented by paying attention to the MSN-Approach implementation model, and the Systems-Approach focus indicator in particular was implemented effectively. Factors that affected the implementation of the Smart Government Policy included the lack of Human Resources, and the lack of features for registering, uploading and downloading files on websites and applications. Based on the results, we can conclude that there are improvements that need to be made in order to support the implementation of the Smart Government Policy in Soppeng Regency, including updating the website and the application, which currently can only provide information about procedures and service requirements, so that the community has to be served manually at the office or location where the service is held. Keywords: implementation, policy, smart government